2000
DOI: 10.1074/jbc.275.18.13645
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Determinants for the Pyruvate Dehydrogenase Component Reaction Mapped with Mutated and Prosthetic Group Modified Lipoyl Domains

Abstract: Efficient catalysis in the second step of the pyruvate dehydrogenase (E1) component reaction requires a lipoyl group to be attached to a lipoyl domain that displays appropriately positioned specificity residues. As substrates, the human dihydrolipoyl acetyltransferase provides an N-terminal (L1) and an inner (L2) lipoyl domain. We evaluated the specificity requirements for the E1 reaction with 27 mutant L2 (including four substitutions for the lipoylated lysine, Lys 173 ), with three analogs substituted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Subsequent studies showed that the interactions between LBD and E1 are more complex and are not attributable to a single determinant on the LBD domain (64 -66). In fact alanine substitutions of residues corresponding to Ile 11 , Gly 12 , and Gly 14 in L1 loop and Thr 50 and Gln 33 in the far end of the hbLBD structure were shown to have marked reduction in the E1 reaction rate (64). Thus, the interaction site between E1 and LBD appears to encompass surfaces that extend from one end to the other in both structures.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent studies showed that the interactions between LBD and E1 are more complex and are not attributable to a single determinant on the LBD domain (64 -66). In fact alanine substitutions of residues corresponding to Ile 11 , Gly 12 , and Gly 14 in L1 loop and Thr 50 and Gln 33 in the far end of the hbLBD structure were shown to have marked reduction in the E1 reaction rate (64). Thus, the interaction site between E1 and LBD appears to encompass surfaces that extend from one end to the other in both structures.…”
Section: Discussionmentioning
confidence: 98%
“…The absence of the lag-phase for the alanine substitution of site 1 and glutamate substitution of sites 2 or 3 (Table I) may indicate the inability of the phosphorylated E1 to undergo the activation during catalysis. Gong et al (49) suggested that it is not the decarboxylation but interaction of lipoyl domain with E1 that facilitates structural changes within E1 and subsequently the efficient reductive acetylation. The negative charge and the size of the phosphoryl group located in the substrate channel could prevent the interaction of E1 with the negatively charged region (Glu-162, Glu-167) of the lipoyl domain (12).…”
Section: Discussionmentioning
confidence: 99%
“…The low K m value of 26 M for the free lipoyl domain indicates that it has appreciable affinity for residues near the active site of E 1 (8). Studies of mutations in the lipoyl domains revealed a specificity loop in which several residues in the lipoyl domain confer specificity on the reductive acylation reaction (29)(30)(31). We have docked the lipoyl domains so that this specificity loop faces the E 1 complex near its active site (Fig.…”
Section: Discussionmentioning
confidence: 99%